Strengthening Market Discipline by Depositors : A TISM and MICMAC Approach - Barve, Pia; Nayak, Sushma (Indian Journal of Finance, 2023)
Purpose: The study aimed at identifying the interrelationships between the different factors that influence market discipline by bank depositors. Given the increasing uncertainty and volatility associated with the banking system, examining the influencers of depositor behavior was necessary. Methodology: Ten determinants were identified through a literature review and confirmed through expert consultation. Furthermore, inter-determinant relationships were established, and a hierarchical structure of the identified determinants was constructed using total interpretive structural modelling (TISM) and Matrice d’Impacts Croisés Multiplication Appliquée á un Classement (MICMAC) analysis. Findings: According to the study, maintaining government guarantees in control and having a solid deposit insurance scheme are essential for the banking sector’s stability. Furthermore, depositor awareness and knowledge are known to achieve effective market discipline. Bank disclosure and transparency contribute significantly to the improvement of market discipline. Additionally, these characteristics encourage additional determined elements for increased attention and surveillance by depositors. Practical Implications: The analysis helped identify determinants according to their ability to influence and get influenced by other determinants. The determinants classified as independent factors, viz., deposit insurance system, knowledge of depositors, and presence of government guarantee, should be strengthened to bring about better market discipline. Originality: Several studies in the past have discussed the importance of market discipline to ensure the efficient functioning of banks. Nevertheless, very few studies have attempted to identify the factors that drive market discipline and their interlinkages, which is a unique contribution of this study.